Motivação de empreendedores em varejo de shopping centers de Curitiba - Biff Netto, Jorge (2016)
*** This study sought to understand the initial motivations of retail entrepreneurs Malls, trying to relativize the conclusions to the theory of motivation by opportunity and necessity (PUSH and PULL theory). In a sample collected in three major shopping centers in Curitiba-PR, respondents in form separate clusters (groups) with particular volitional characteristics among members, resulting in four different groups. Besides entrepreneurs motivated by opportunity and necessity, this researcher indicated the creation of two new drivers of groups, by unemployment and by business diversification, the less significant and that formed by the largest number of members. In a second step, we sought to identify within the groups formed, what factors led to its decision to undertake, and therefore which most makers related to each group.***.